Finetuning XLM-Roberta Pretrained Models For Question Answering In Hindi - Nirja D Shah; Jyoti Pareek (International Journal of Computational and Experimental Science and Engineering, 2025)
The paper intends to explore the development of a Hindi QA system using XLM-RoBERTa, trained on the Hindi subset of the chaii dataset. It tries to bridge the performance gap existing between low resource languages such as Hindi and high resource counterparts like English in the QA systems domain. We validate the model with systematic experimentation over a set of hyperparameters. The results reveal that relatively smaller learning rates, especially 0.00002, even with batch size 8, greatly enhance the performance with average BERTScore of 88.11. On the contrary, higher learning rates uniformly resulted in decreases in model performance. The batch size also mattered to performance but much less so than learning rate as lower batch sizes did not significantly degrade performance at lower learning rates. Further extensions to the above metrics depict good performance for smaller values of learning rates, with cases up to 21.07% above a BLEU score greater than 80 and 37.72% of cases with ROUGE1 F1 above 80. Such cases emphasize fine-tuning to be very important in QA tasks in low-resource languages. This paper contributes to understanding how QA systems can be optimized for Hindi and provides a benchmark for future research in this area